Improving the electrochemical properties of MXene Ti3C2 multilayer for Li-ion batteries by vacuum calcination. (1st March 2018) - Kong, Fanyu; He, Xiaodong; Liu, Qianqian; Qi, Xinxin; Zheng, Yongting; Wang, Rongguo; Bai, Yuelei
Abstract: The electrochemical properties of MXene Ti3 C2 multilayer for Li-ion batteries were improved greatly by vacuum calcination, after systematically evaluating its thermal stability in different atmosphere in details. In air, the as-prepared Ti3 C2 could not be oxidized up to 429.9 °C and the rutile-TiO2 would remain as the oxidation product at 1200 °C. The surface functional groups especially F groups can be eliminated by heat treatment. After vacuum calcination at 400 °C, the Ti3 C2 show much higher capacities due to the removal of OH groups (126.4 mAh·g −1 at 1C), and exhibited excellent rate capability. Besides, the formation of TiO2 nanoparticles at 700 °C further increases the first coulombic efficiency (62%) and capacity retention after 100 cycles (97%). In contrast, the dense microstructures of resulting TiC x formed after calcination at 1000 °C results in the worst electrochemical properties. This paper presented a relatively simple and easily scalable post-treatment for improving the electrochemical properties of MXene, and demonstrated a great potential of Ti3 C2 of using as anode material for Li-ion batteries.